Kualitas Religius dan Kesehatan Psikologis pada Lansia yang Mengikuti Kajian Rohani - Fani Masruroh; Hielmi Anjaini Rahma (Da'wah Faculty of UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Elderly people in old age experience physical changes, such as decreased cognitive function, decreased muscle mass or weakened stamina, decreased organ function, decreased vision and hearing, and other changes. Elderly people can also experience psychological and emotional changes. These changes can cause loneliness, the loss of a life partner, and changes in sleep patterns and mood, so psychological treatment is needed to maintain the quality of life in old age. One way of psychological treatment for the elderly is by improving the religious quality of the elderly. Religious qualities can provide seniors with a spiritual and ethical framework that provides a sense of purpose in seniors' lives. This research is to explore the religious qualities and psychological health of elderly people who take part in spiritual studies at Balai Muslimat Kalisalak. This research was carried out qualitatively using a field approach (field research) with study leaders and elderly congregation members at the Kalisalak Muslimat Hall by analyzing the data and then discussing it. The results of the research show that psychological health in the elderly is very important to maintain to maintain the quality of life in order to live a happy life. Several factors that influence the psychological health of the elderly are physical health, social relationships, independence, self-acceptance, and spiritual aspects. Spiritual studies have an important role in increasing the development of personal potential and improving the quality of religious psychological health. Some of the positive effects obtained to improve religious quality include social support, meaning of life goals, coping and divinity, hope, and optimism. This research also provides good suggestions for improving the quality of life in old age and improving psychological health in old age. Lansia dalam menjalani masa tua mengalami perubahan fisik, seperti penurunan fungsi kognitif, penurunan masa otot atau melemahnya stamina, penurunan fungsi organ, penurunan pengelihatan dan pendengaran, serta perubahan-perubahan lainya. Lansia juga dapat mengalami perubahan psikologis dan emosional. Perubahan ini dapat menyebabkan kesepian, kehilangan pasangan hidup, perubahan pola tidur dan mood, sehingga perlunya penanganan psikologis untuk menjaga kualitas hodupnya di masa tuanya. Penanganan psikologis untuk lansia salah satunya dengan cara meningkatkan kualitas religius lansia. Kualitas religius dapat memberikan lansia sebuah kerangka spiritual dan etis yang memberikan rasa tujuan dalam kehidupan lansia. Penelitian ini untuk mengeksplorasi Kualitas Religius dan Kesehatan Psikologis pada Lansia yang Mengikuti Kajian Rohani di Balai Muslimat Kalisalak. Penelitian ini dlakukan dengan kualilatif menggunakan pendekatan lapangan (fiels research) dengan pemimpin pengajian dan para jama’ah lansia di Balai Muslimat Kalisalak dengan melakukan analisis data kemudian dilakukan pembahasan. Hasil penelitian adalah Kesehatan psikologis pada lansia sangat penting untuk dipertahankan untuk menjaga kualitas hidup agar menjalani hidup yang bahagia. Beberapa faktor yang mempengaruhi kesehatan psikologis lansia adalah kesehatan fisik, hubungan sosial, kemandirian, penerimaan diri, dan aspek spiritual. Kajian Rohani memiliki peranan penting dalam meningkatkan pengembangan potensi diri dan meningkatkan kualitas kesehatan psikologis secara religius. Beberapa efek positif yang didapatkan untuk meningkatkan kualitas religius diantaranya yaitu, dukungan sosial, makna tujuan hidup, coping dan ketuhanan, harapan dan optimisme. Dalam penelitian ini juga disampaikan saran-saran yang baik untuk meningkatkan kualitas hidup di masa tua serta meningkatkan kesehatan psikologis pada masa tua.